Self-Immobilization of Rhizopus oligosporus on Shrimp Shell Chitin Matrix for Troso Fabric Dyeing Wastewater Adsorption - Kania Okta Wijanaputri; Fidia Fibriana; Amnan Haris; Andhina Putri Heriyanti (Life Science, 2026)
The Troso fabric industry in Indonesia contributes significantly to the national economy but also produces liquid waste containing chemical dyes. Liquid waste from the Troso weaving industry exceeds wastewater quality standards, including BOD, COD, and pH, and can pollute the environment if not managed properly. Chemical and physical methods for wastewater removal in dyeing have already been used, but still have limitations, such as being expensive and causing environmental side effects. Therefore, the biological method is preferred to overcome these problems. The present study aims to develop a Rhizopus oligosporus mycelium immobilization system using chitin from shrimp shells and to test its adsorption capacity for removing a dye agent (direct yellow) from Troso fabric dye-contaminated wastewater. The immobilization was performed using both solid-state and submerged techniques in potato dextrose broth (PDB). The one-factor-at-a-time (OFAT) method was used to determine the optimal pH and the optimal number of biosorbents for efficient dye removal. The results showed that the optimal immobilization system was the solid-state technique, which yielded a well-developed hyphal structure on the chitin surface with a cell-loading capacity (CLC) of 1.19 gbiomass/gmatrix. In the adsorption capacity (qe) assay, the results showed that pH 7.0 and 3 bio-balls application provided the highest adsorption capacity of 122.608 mg/g and 64.73% color removal. This study shows the potential use of immobilized chitin as a biosorbent for effectively treating textile wastewater.